PERLINDUNGAN HUKUM TERHADAP HAK PEKERJA YANG TIDAK DIBAYARKAN DALAM PEMUTUSAN HUBUNGAN KERJA: DALAM PERSPEKTIF HUKUM KETENAGAKERJAAN - Padilah, Muhamad; Rahmatiar, Yuniar; Abas, Muhamad (Fakultas Ilmu Sosial dan Humaniora, 2024)
Termination of employment (PHK) often triggers conflicts between workers and employers, especially when regulations are violated, which can lead to financial and psychological harm for workers. To ensure the protection of workers' rights in PHK cases, the enforcement of legal protection is crucial. For example, the unilateral dismissal case experienced by Riyani Chairunnisa from PT. Selong Selo Lombok was annulled by law because it did not comply with Article 151 of Law Number 13 of 2003 and Article 151 of Law Number 06 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation. This research aims to analyze the legal protection and judicial considerations for workers who experience unilateral dismissal without severance pay. The method used is a normative juridical approach through literature study and qualitative analysis of primary, secondary, and tertiary legal materials. The research results show the importance of adequate legal protection for workers who are unilaterally dismissed and the significance of judicial considerations in accordance with Law No. 13 of 2003 and Law No. 06 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation.